Overcoming Poststructuralism - O'Loughlin, A. author. aut Link
V, 281 p.
Keywords: Through the use of a poststructuralist perspective, Antony O'Loughlin challenges the most basic tenets of International Relations Theory and deploys Rawlsian ideas of public reason in conjunction with Kratochwil's conceptions of practical reason in order to put forward a theory that overcomes the challenges posed by poststructuralism.